Characterization of a phage-plasmid hybrid (phasyl) with two independent origins of replication isolated from Escherichia coli. - Gielow, A (1991)
The phage-plasmid hybrid phasyl can replicate as a phage in the presence of a filamentous phage of Escherichia coli (M13, fl, fd). The extragenic region of phasyl shows homology with the plus and the minus origins of filamentous phages. Insertion of a Cmr fragment into the plus origin or of a Kmr fragment into the minus origin resulted in a reduced transduction frequency, while insertion into other parts of the extragenic region did not. This suggests that phagelike replication of phasyl is mediated by an origin that coincides with the two homologous elements in the extragenic region. Autonomous replication of phasyl occurs from a second origin (oriA) that is located between positions 297 and 636. This fragment mediates replication if the Arp protein is supplied in trans. Arp is the only phage-encoded protein and is essential for plasmidlike replication. No sequence homology to other known origins was found. Phasyl derivatives with either one of the two origins inactivated can be rescued via the alternative replication mode, suggesting that the two replication pathways are independent.